Rare-earth-tantalate high-entropy ceramics with sluggish grain growth and low thermal conductivity. Issue 8 (15th April 2022) - Li, Chen; Meng, Bin; Fan, Sining; Ping, Xinyu; Fang, Congcong; Lin, Wu; Chen, Yingquan; Zhang, Han
Abstract: A series of rare-earth-tantalate high-entropy ceramics ((5RE0.2 )Ta3 O9, where RE = five elements chosen from La, Ce, Nd, Sm, Eu and Gd) were prepared by conventional sintering in air at 1500 ° C for 10 h. The (5RE0.2 )Ta3 O9 high-entropy ceramics exhibit an orthogonal structure and sluggish grain growth. No phase transition occurs in the test temperature of 25–1200 ° C. The thermal conductivities of all (5RE0.2 )Ta3 O9 ceramics are in the range of 1.14–1.98 W m −1 K −1 at a test temperature of 25–500 ° C, approximately half of that of YSZ. The sample of (Gd0.2 Ce0.2 Nd0.2 Sm0.2 Eu0.2 )Ta3 O9 exhibits a low glass-like thermal conductivity with a value of 1.14 W m −1 K −1 at 25 ° C. The thermal expansion coefficient of (5RE0.2 )Ta3 O9 ceramics ranges from 5.6 × 10 −6 to 7.8 × 10 −6 K −1 at 25–800 ° C, and their fracture toughness is high (3.09–6.78 MPa·m 1/2 ). The results above show that (5RE0.2 )Ta3 O9 ceramics could be a promising candidate for thermal barrier coatings.